Formation of Communicative Literacy in Preschool Educational Institutions - Nodira Xayrullayevna Djumanova (Academia One Publishing, 2023)
In this article, the task of a psychologist in the field of pre-school education, the priority tasks of psychological service, the psychological characteristics of children of preschool age, the opinions of theoretical scientists in this regard.
Keywords: preschool organization; upbringing; healthy lifestyle